Teach yourself visually macOS High Sierra - McFedries, Paul (Teach yourself visually, 2018)
"Are you a visual learner? Do you prefer instructions that show you how to do something--and skip the long-winded explanations? If so, then this book is for you. Open it up and you'll find clear, step-by-step screen shots that show you how to tackle more than 160 macOS High Sierra tasks. Each task-based spread covers a single technique, sure to help you get up and running on macOS High Sierra in no time"-- Page 4 of cover.